(3Jbjje GdCSge h GdSfOGJ (B:s (3eONd GdgfOSI GdeGdjI (B/s - (3GdMfGhj, eMeO UGdMs; (3fgGd, aQjO eUWais ((3GdGScfOQjI(B: s (3GdecJH GdLGeYj GdMOjK(B, s, 2007)
(3ebOeI aj CSGSjGJ GdGSJKeGQ h TQGA h HjY GdGhQGb GdeGdjI h Jbjje GdCSge GdYGOjI h GdJMdjd Gdafj h JMdjd GdSfOGJ h fehPL JSYjQ GdCUhd GdQCSeGdjI h EOGQI eMGaX GdChQGb GdeGdjI h Mbhb GdGNJjGQ h YbhO GdeHGOdI h GdYbhO GdeSJbHdjI h GdGSJKeGQ YHQ GdGfJQfJ(B.s
(3eQGLY U(B.429s
Keywords: (3GdCSges; (3GdSfOGJs